GAMBARAN PENGETAHUAN DAN SIKAP TENTANG SEKS USIA REMAJA DI SMK PARIWISATA X BADUNG - Ni Putu Fridayanti Pratiwi; Ida Arimurti Sanjiwani; I Kadek Saputra (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Adolescence is a period of transition from children to adulthood. One of the changes that occur in adolescence is primary and secondary sexual changes. Physical changes in adolescents need to be balanced with knowledge about reproductive health. Low information about reproductive health can potentially increase the incidence of adolescent sex. This study aims to look at the description of knowledge and attitudes of adolescents about adolescent sex at SMK Pariwisata X Badung. The research design is quantitative descriptive with an observational approach. This study uses stratified random sampling technique to take a sample of 313 students in SMK Pariwisata X Badung. The data were collected using questionnaires. The results of the study found 193 students (61.7%) had good knowledge about adolescent sex and 280 students (89.5%) had a good attitude towards adolescent sex. The suggestions in this study are expected that this study can be a foundation for schools in making policies as an effort to increase and maintain knowledge about adolescent sex.